PELAKSANAAN TRANSAKSI GADAI TERHADAP TANAH ULAYAT DI KABUPATEN PADANG PARIAMAN - , Irwan Rais; , Sulastriyono, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this study is to investigate the transaction lien lands in the district of Padang Pariaman, and settlement of disputes aimed at how the implementation lien mortgage transactions in the district of Padang Pariaman, and the causes of indigenous communities in Padang pariaman still tend to do the pledge of land. This research is using the empirical method of approach used to analyze the law is seen as the behavior of people who figured in public life who always interact and relate in a social aspect as well as mnganalisa also the application of customary law that occurred in the life of the Minangkabau people of pawning land. Pledge Against Implementation of Communal Land transactions in Padang District pariaman. Communal Land Types of Communal Land Rajo, Communal Land Nagari, indigenous tribe, indigenous People. District Community Padang Pariaman do pawn lands on condition of prsetujun, mamak chief beneficiary, mamak, panghulu people, panghulu tribe, old urang customary, and villages are known members of the government. Implementation lien lands in the district of Padang Pariaman, Koto Piliang Implementation consists of three respondents based on autocracy system, system of government held by the king's power, transaction execution lien on keselaran Chaniago body consists of three respondents, this system based on the system of democracy or deliberation to reach consensus. Kelarasan Lareh Nan Long consist of one respondent, is based on a mix of Koto Kelarasan Caniago Piliang and Bodi. Implementation gadainya with koto Piliang and Bodi Caniago. In the event the dispute is resolved in mesyawarah and consensus so that a sense of kinship can be maintained. Cause people still do the pledge of Padang Pariaman lands until now because the function lien lands in the District of Padang Pariaman utilized for the welfare of the child as a niece or nephew of land reserves for a growing child later on from generation to generation.